2020
DOI: 10.1002/jcb.29587
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor RUNX3 promotes CD8+ T cell recruitment by CCL3 and CCL20 in lung adenocarcinoma immune microenvironment

Abstract: Considering the existence of immune-desert in tumor microenvironment, the clinical efficacy of immunotherapy for lung adenocarcinoma is limited. This study aims to investigate the ability of transcription factors in regulating tumor immune microenvironment in lung adenocarcinoma. RNA-seq data were collected from the The Cancer Genome Atlas database. The relationships between transcription factors and immune infiltrates were assessed. Runtrelated transcription factor 3 (RUNX3)-associated immune pathways were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Previous studies have reported that members of the RUNX gene family have crucial roles in immune reaction and immune cell in ltration. For example, RUNX3 was shown to promote CD8 + T cell recruitment in the LUAD immune microenvironment [31]. To better understand the association between the RUNX gene family and immune cell in ltration, we investigated the relationships between the RUNX family and immune subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that members of the RUNX gene family have crucial roles in immune reaction and immune cell in ltration. For example, RUNX3 was shown to promote CD8 + T cell recruitment in the LUAD immune microenvironment [31]. To better understand the association between the RUNX gene family and immune cell in ltration, we investigated the relationships between the RUNX family and immune subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…78 Song et al found that RUNX3 upregulated CCL3 and CCL20 (Table 3) and thus promoted CD8 + T cell recruitment. 78 Interestingly, the downregulation of RUNX3 reduced CCL3 and CCL20 expression and CD8 + T cell infiltration. 78 Li et al 76 uncovered the role of miR-301a in antitumor immunity.…”
Section: Cytotoxic T Cellsmentioning
confidence: 98%
“…Upregulation of CCR5 and CCR6 receptors occurred in CD8 + effector T cells 78 . Song et al found that RUNX3 upregulated CCL3 and CCL20 (Table 3) and thus promoted CD8 + T cell recruitment 78 . Interestingly, the downregulation of RUNX3 reduced CCL3 and CCL20 expression and CD8 + T cell infiltration 78 …”
Section: T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Runx-CBFb complex binds to the Ccl5 enhancer and, together with the chromatin organizer SATB1, restrains the expression of Ccl5 (157). Positive regulation of CCL3 and CCL20 by RUNX3 contributes to the recruitment of CD8 T cells into the microenvironment of lung adenocarcinoma, supporting antitumor immunity (158).…”
Section: Chemokinesmentioning
confidence: 99%